PENINGKATAN HASIL BELAJAR KOGNITIF SENI MUSIK MELALUI PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT - Pangestu, Steven Hasan; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research was based on the poor cognitive learning achievement of seventh-grade students in SMP Negeri 9 Pontianak. The aim of this research was to describe the design, the process, and the cognitive learning achievement in music lesson which students had learned using Teams Games Tournament learning method. This research used descriptive method with a form of classroom action research. Data in this research were collected by observation and test. Research instruments included the sheet of observation manual and learning achievement test. The result of this research showed that the studentsâ€™ cognitive learning achievement had been increased during the process. At the first cycle, the sheet of observation manual scored 93.57% with a rate of excellent. There are 21 students (53.85%) who surpassed the test. The average test score of this cycle was 73.85 with a rate of average. At the second cycle, the sheet of observation manual scored 95% with a rate of excellent. There were 37 students (92.5%) who surpassed the test. The average test score of this cycle was 94.5 with a rate of high.Â Keywords: Cognitive Learning Achievement, Music Lesson, Teams Games Tournament